MicroRNA-34a Promotes Ischemia-Induced Cardiomyocytes Apoptosis through Targeting Notch1. (28th February 2022) - Pan, Jialin; Zhou, Lili; Lin, Cong; Xue, Weihao; Chen, Peng; Lin, Jiafeng
Abstract : Myocardial apoptosis occurs during myocardial ischemia. This study aimed to determine the effect of microRNA-34a (miR-34a) in ischemia-induced myocardial apoptosis. Mainly, SD rats were subjected to myocardial ischemia by ligaturing the left anterior descending branch of coronary artery. After rats had myocardial infarction, HE staining and TUNEL staining confirmed a significant increase in apoptosis. The expression of miR-34a was noticeably upregulated, while the expression of Notch1 was downregulated. An increase in caspase-3 and a decrease in Bcl-2/Bax ratio were observed in myocardium. Similar results were observed in the in vitro model of cardiomyocyte ischemia and anoxia of this study. When rat cardiomyocytes were administered with serum starvation and microaerophilic system, apoptosis-related proteins were significantly increased. However, transfecting the miR-34a inhibitor into the cardiomyocyte before the serum starvation and hypoxia treatment could increase the ratio of Bcl-2/Bax and downregulate the expression of caspase-3, as well as prevent cardiomyocytes from apoptosis. As opposed to the abovementioned points, the upregulation of miR-34a expression by transfecting miR-34a mimics induced Notch1 reduce and apoptosis-related proteins increase apparently, while upregulation of Notch1 could stimulate apoptosis attributed to miR-34a. Mechanistically, we demonstrated that Notch1 is a direct target of miR-34a. In conclusion, our current results suggested that miR-34a significantly stimulates ischemia-induced cardiomyocytes apoptosis by targeting Notch1.